A highly contiguous genome assembly of red perilla (Perilla frutescens) domesticated in Japan. (16th November 2022) - Tamura, Keita; Sakamoto, Mika; Tanizawa, Yasuhiro; Mochizuki, Takako; Matsushita, Shuji; Kato, Yoshihiro; Ishikawa, Takeshi; Okuhara, Keisuke; Nakamura, Yasukazu; Bono, Hidemasa
Abstract: Perilla frutescens (Lamiaceae) is an important herbal plant with hundreds of bioactive chemicals, among which perillaldehyde and rosmarinic acid are the two major bioactive compounds in the plant. The leaves of red perilla are used as traditional Kampo medicine or food ingredients. However, the medicinal and nutritional uses of this plant could be improved by enhancing the production of valuable metabolites through the manipulation of key enzymes or regulatory genes using genome editing technology. Here, we generated a high-quality genome assembly of red perilla domesticated in Japan. A near-complete chromosome-level assembly of P . frutescens was generated contigs with N50 of 41.5 Mb from PacBio HiFi reads. 99.2% of the assembly was anchored into 20 pseudochromosomes, among which seven pseudochromosomes consisted of one contig, while the rest consisted of less than six contigs. Gene annotation and prediction of the sequences successfully predicted 86, 258 gene models, including 76, 825 protein-coding genes. Further analysis showed that potential targets of genome editing for the engineering of anthocyanin pathways in P. frutescens are located on the late-stage pathways. Overall, our genome assembly could serve as a valuable reference for selecting target genes for genome editing of P. frutescens .